PERCEPTIONS OF HUMAN RESOURCES MANAGERS ON TELECOMMUTING CONCEPT: Implementation in Malaysian Firms - Karia, Noorliza; Zainuddin, Yuserrie; Abu Hassan Asaari, Muhammad Hasmi (Gadjah Mada International Journal of Business, 2003)
Telecommuting concept has been a new phenomenon for most ofMalaysian firms, especially for human resource managers. Further, the drive towards promoting the telecommuting concept need to be done as part of paradigm change as Malaysia is becoming an industrialized nationâVision 2020 of the Prime Minister. This study was conducted on the Malaysian human resource managers in representing their firmâs stand on the telecommuting concept. The purpose of this paper is to explore the level of acceptance of the telecommuting concept by the human resource managers. It was discovered that high percentage of the human resource managers shown their concern on the acceptance of the telecommutingconcept.